EFEKTIFITAS EKSTRAK HERBAL TERHADAP PROSES PENYEMBUHAN KELINCI YANG TERINFEKSI KOKSIDIOSIS - Annistia Rahmadian Ulfah; Mohandas Indradji; Diana Indrasanti; M. Nur Ichwan; E Rokayah (ANGON: Journal of Animal Science and Technology, 2022)
Background. Coccidiosis in rabbits, caused by the parasite Eimeria sp., inflicts gastroinstestinal problems mainly diarrhea and gastroinstestinal bleeding. This study aims to research about the effectiveness of herbal extracts combination (garlic, papaya seeds, and banana stems) in the recovery process of rabbits infected with coccidiosis, seen from the large number of platelets, fibrinogen, and whether there is an increase in body weight. Materials and methods. A total of 24 Rex breed rabbits weighing ± 600 – 700 grams, identified as having coccidiosis, were monitored for four weeks using individual cage system and given a combination of regular food and herbal extracts of 0, 20, 40, 60, and 100 mg. The study was conducted in a completely randomized design using 5 treatments and 4 replications. Each herb was extracted using the maceration method. The Rabbits’ number of platelets, fibrinogen and body weight were taken as a data and analyzed for variance. Results. The results for the addition of the herbal extracs showed different result for each data cathegory. For the number of platelets, the highest average was 523.25 ± 76.05 x103/µL at the dose of 60 mg and the lowest was 329.00 ± 276.48 x103/µL at a dose of 20 mg. For Fibrinogen the highest and lowest averages were 0.35 ± 0.24 g/dL and 0.18 ± 0.05 g/dL, namely at doses of 60 mg and 100 mg. For the average body weight the highest average was obtained at a dose 20 mg of a combination of herbal extracts, namely 744.56 ± 45.15 g/head. Conclusion. Giving a combination of garlic herbal extracts, papaya seeds, and banana stems to rabbits infected with coccidiosis does not effectively improve the healing process.